The Bumper Book of Crafty Activities : 100+ creative ideas for kids (Search Press, 2012)
With step-by-step photographs and easy-to-follow instructions, this boredom-busting book shows children how to create more than 100 great projects using readily available materials. Kids can learn collage, clay modeling, beadwork, decorative painting, papermaking, paperfolding, printing, creative lettering, mosaics, papier mache, origami, and cardmaking--all in seven steps or fewer. Each new section has an introduction on the history of the craft and the techniques employed. There are also further ideas and developments on the projects to inspire children and adults to get even more creative.